Fabrication of Carbon-Like, π-Conjugated Organic Layer on a Nano-Porous Silica Surface - Hiroki Noguchi; Marzia Sultana; Nanami Hano; Yutaka Kuwahara; Makoto Takafuji; Shoji Nagaoka; Hongdeng Qiu; Hirotaka Ihara (Nanomaterials, 2020)
This paper presents a new type of black organic material-porous silica composite providing an extremely highly selective adsorption surface. This black composite was prepared by lamination on nano-sized pores with a carbon-like, π-extended structure, which can be converted via the on-site polymerization of 1,5-dihydroxynaphthalene with a triazinane derivative and a thermally induced condensation reaction with denitrification. This bottom-up fabrication method on porous materials had the great advantage of maintaining the pore characteristics of a raw porous material, but also the resultant black surface exhibited an extremely high molecular-shape selectivity; for example, that for trans- and cis-stilbenes reached 14.0 with the black layer-laminated porous silica, whereas it was below 1.2 with simple hydrophobized silica.